Study guides

Q: How do you i get 39 using 6 6 6 6 6?

Write your answer...

Submit

Related questions

Assuming that you can only use each number once, then one solution is :- 6 x (22 - 2 - 39/3) = 6 x (20 - 13) = 6 x 7 = 42

6% of 39 = 6% * 39 = 0.06 * 39 = 2.34

-39 + 6 = -33

39

39 divided by 6 is 6.5

6.5

45-39 = 6

39 - 14 - 6 = 19

39/6 = 13/2

6.5

The LCM of 6 and 39 is 78

2x + 6 + 9x = 39 11x + 6 = 39 11x = 39 - 6 11x = 33 x = 3

It is not clear what you are asking, so here are possible answers: 39 x 6.23 = 242.97 39 x 623 = 24297 39 x 6 + 23 = 257 39 x 6 - 23 = 211 39 x 6 ÷ 23 = 10.17391 39 x 6 x 23 = 5382

No. 39 is odd but 6 is even and all multiples of 6 are even.

3, Its the largest number that goes into both 6 and 39 evenly.

The GCF of 6, 39, and 45 is 3.

You memorize the multiplication facts that 6 times 6 is 36. This tells you that six goes into 39 6 times with 3 left over since 39-36 = 3.

It is: 39/2 = 19.5 inches

6 is even. 33 is odd. 33+6=39. 39 is odd.

39 ÷ 6 = 6 with remainder 3

Try: 3 times 13 = 39

[[(13√9)/(19-(3+3))]/3]=((39/19-6)/3)=((39/13)/3)=(3/3)=1

39/18 = 13/6 = 2 1/6

The least common multiple of the numbers 39 and 6 is 78.

(33 + 3!) / 3 = (33 + 6) / 3 = 39 / 3 = 13.